FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETIDAKPEDULIAN KESEHATAN REPRODUKSI REMAJA DI WILAYAH KERJA PUSKESMAS DANAU MARSABUT SIPIROK TAHUN 2020 - Niapina, Yesi Omelika (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2021)
Adolescents are very at risk of reproductive health problems such as premarital sexual behavior and indifference to their reproductive health. The aim of this study was to analyze factors related to adolescent reproductive health indifference in the Working Area of ​​the Danau Marsabut Sipirok Health Center in 2020. This type of research is a correlation analytic study. with cross sectional method. The number of samples was determined by purposive sampling as many as 93 people taken from the population aged 12-18 and willing to be the sample. The data were collected using a questionnaire which was then analyzed univariately, bivariately and multivariately. Characteristics of female respondents were 55.9% and male 44.1% and the mean age was 15, 25 years. The bivariate test results obtained that only the variables had a significant relationship with reproductive health indifference; knowledge (p value = 0.015), and awareness (p value = 0.002), while access to information was not significantly related (p value = 0.283). The multivariate test showed that the awareness variable had the strongest relationship with reproductive health indifference to adolescents in the work area of ​​the Danau Marsabut Health Center with a value of Exp.B = 3,729. It is recommended that the Danau Marsabut Health Center develop activities that can increase adolescent awareness of their reproductive health in a creative way and illustrate cases appropriate to adolescent age groups.